Excavating Emotion: Emotional Metaphors in Incubus’ Song “Dig” - Muhammad Hamzah; Aqshal Alifa Mahmud; Cut Fitrah Ashyfa; Rahmadsyah Rangkuti (Universitas Nurul Jadid, 2026)
This research was written in order to analyze the lyrics of a song by American rock band Incubus. The purpose of this research is to discover what types of metaphors are present in the lyrics of the song, and how metaphors are used by songwriters to structure their lyrics and to give meaning in their worldplay. Previous research on this topic has primarily concentrated on categorising types of figurative language, with insufficient emphasis on the role of metaphor as a cognitive mechanism for representing emotion. To solve this, the research will focus on analysis of metaphor in use as a cognitive tool with Conceptual Metaphor theory as a framework for analysis.This study utilises a qualitative descriptive methodology, employing the official lyrics as data. Metaphorical expressions are discerned and examined through the mapping of source domains (concrete metaphors) onto target domains (abstract metaphors), succeeded by cognitive interpretation. There are two subjects used in this research. The first subject is a song by Incubus which is Dig from their 2006 album Light grenades. The second subject is George Lakoff and Mark Johnson's (1980) Conceptual Metaphor Theory within a cognitive stylistic framework. The results show 16 metaphorical expressions, which can be divided into three groups: structural (37.5%), orientational (31.25%), and ontological (31.25%). Structural metaphors are the most common. Thus it can be argued that the usage of structural metaphors reflects a tendency to relate abstract things in terms of concrete things like physical actions and processes. Orientational and ontological metaphors depict emotional states through spatial and entity-centric mappings. The study concludes that metaphor serves beyond a mere linguistic tool and is a cognitive mechanism that facilitates the comprehension of intricate emotional experiences through embodied and relatable constructs.Keywords: Metaphor, Cognitive stylistics, Emotional expression, Song lyrics, Conceptual Metaphor Theory